Versatile roles of polyamines in improving abiotic stress tolerance of plants - Shao, Jinhua; Huang, Kai; Batool, Maria; Idrees, Fahad; Afzal, Rabail; Haroon, Muhammad; Noushahi, Hamza Armghan; Wu, Weixiong; Hu, Qiliang; Lu, Xingda; Huang, Guoqin; Aamer, Muhammad; et al. (Frontiers in Plant Science, 2022)
In recent years, extreme environmental cues such as abiotic stresses, including frequent droughts with irregular precipitation, salinity, metal contamination, and temperature fluctuations, have been escalating the damage to plants’ optimal productivity worldwide. Therefore, yield maintenance under extreme events needs improvement in multiple mechanisms that can minimize the influence of abiotic stresses. Polyamines (PAs) are pivotally necessary for a defensive purpose under adverse abiotic conditions, but their molecular interplay in this remains speculative. The PAs’ accretion is one of the most notable metabolic responses of plants under stress challenges. Recent studies reported the beneficial roles of PAs in plant development, including metabolic and physiological processes, unveiling their potential for inducing tolerance against adverse conditions. This review presents an overview of research about the most illustrious and remarkable achievements in strengthening plant tolerance to drought, salt, and temperature stresses by the exogenous application of PAs. The knowledge of underlying processes associated with stress tolerance and PA signaling pathways was also summarized, focusing on up-to-date evidence regarding the metabolic and physiological role of PAs with exogenous applications that protect plants under unfavorable climatic conditions. Conclusively, the literature proposes that PAs impart an imperative role in abiotic stress tolerance in plants. This implies potentially important feedback on PAs and plants’ stress tolerance under unfavorable cues.